2022
DOI: 10.32604/phyton.2022.016231
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Growth, Photosynthetic Pigments, Cell Viability, Lipid Peroxidation and Antioxidant Defense System in Two Varieties of Chickpea (Cicer arietinum L.) Subjected to Salinity Stress

Abstract: Salinity is one of the most severe abiotic stresses for crop production. The present study investigates the salinityinduced modulation in growth indicators, morphology and movement of stomata, photosynthetic pigments, activity of carbonic anhydrase as well as nitrate reductase, and antioxidant systems in two varieties of chickpea (Pusa-BG5023, and Pusa-BGD72). On 20 th day of sowing, plants were treated with varying levels of NaCl (0, 50, 100, 150 and 200 mM) followed by sampling on 45 days of sowing. Recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“… 40 The decrease in chlorophyll content can be attributed to the increase of chlorophyll degradation under stress condition. 41 , 42 In our findings the chlorophyll content of tomato leaves was decreased under sub-optimal temperature stress and such decrease was greater in S708 than in T722. Similarly, previous study also found that there were greater decrease of chlorophyll a and b contents in low temperature sensitive common bean genotype than in tolerant one.…”
Section: Discussionsupporting
confidence: 56%
“… 40 The decrease in chlorophyll content can be attributed to the increase of chlorophyll degradation under stress condition. 41 , 42 In our findings the chlorophyll content of tomato leaves was decreased under sub-optimal temperature stress and such decrease was greater in S708 than in T722. Similarly, previous study also found that there were greater decrease of chlorophyll a and b contents in low temperature sensitive common bean genotype than in tolerant one.…”
Section: Discussionsupporting
confidence: 56%
“…3A). This may be due to rise in the level of Na + , MDA, and H 2 O 2 , disrupting chloroplast membrane stability and causing degradation of the protein-pigment-lipid complex 56 . Exogenous application of melatonin reversed the downward trend and promoted plant growth, biomass, and chlorophyll contents (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further, chlorophyll and carotenoids are necessary for plant growth and development and for the synthesis of photosynthetic products. Under salt stress, chlorophyll synthesis is prevented, which will directly affect photosynthesis, slow plant growth, and reduce yield 40 , 41 . In this experiment, during NaCl stress, the chlorophyll a, chlorophyll b, carotenoids, and total chlorophyll contents of the two rice varieties were significantly decreased (Fig.…”
Section: Discussionmentioning
confidence: 99%